Blast-resistant highway bridges : design and detailing guidelines - Williamson, Eric B., 1968- (Report (National Cooperative Highway Research Program) ;, 2010)
Explores code-ready language containing general design guidance and a simplified design procedure for blast-resistant reinforced concrete bridge columns. The report also examines the results of experimental blast tests and analytical research on reinforced concrete bridge columns designed to investigate the effectiveness of a variety of different design techniques.